DESAIN DAN IMPLEMENTASI DARI PENGENDALIAN GERAK PORTABLE HANDY PLASMA CUTTING BERDASARKAN SUMBU X DAN Y - Kukuh Widarsono, Mohammad Nur, Ahlan Fiambrih (Techno Bahari, 2020)
In the industrial world the process of making household appliances is very much needed cutting tools, one of them is in metal raw materials. Given the demand for these goods very much with various forms. Therefore technology is needed in the form of automatic plate cutting machines to facilitate the work in the design of difficult items. Making this machine by modifying the Handy Portable Plasma Cutting into automatic motion of 2 axes, namely x and y. Using the grbl controller application as a human machine interface and functions as a sender of the g-code generated design drawings that will be cut against the controller. In this study there are operations to determine the position of the point (0,0) and for automatic operation using a stepper motor. In this study the presentation results obtained an average error obtained was 0.7% based on many experiments. And the mechanicals and materials used are not good for long-term durability.